Anxiety sensitivity facets in relation to tobacco use, abstinence-related problems, and cognitions in treatment-seeking smokers. (May 2016) - Guillot, Casey R.; Leventhal, Adam M.; Raines, Amanda M.; Zvolensky, Michael J.; Schmidt, Norman B.
Abstract: Anxiety sensitivity (AS)—fear of anxiety-related experiences—has been implicated in smoking motivation and maintenance. In a cross-sectional design, we examined AS facets (physical, cognitive, and social concerns) in relation to tobacco use, abstinence-related problems, and cognitions in 473 treatment-seeking smokers. After controlling for sex, race, age, educational attainment, hypertension status, and neuroticism, linear regression models indicated that AS physical and cognitive concerns were associated with tobacco dependence severity (β = .13–.14, p < .01), particularly the severity of persistent smoking regardless of context or time of day (β = .14–.17, p < .01). All three AS facets were related to more severe problems during past quit attempts (β = .23–.27, p < .001). AS cognitive and social concerns were related to negative affect reduction smoking motives (β = .14, p < .01), but only the social concerns aspect of AS was related to pleasurable relaxation smoking motives and positive and negative reinforcement-related smoking outcome expectancies (β = .14–.17, p < .01). These data suggest that AS physical and cognitive concerns are associated with negative reinforcement-related smoking variables (e.g., abstinence-related problems), whereas the social concerns aspect of AS is associated with positive and negative reinforcement-related smoking variables. Together with past findings, current findings can usefully guide AS-oriented smoking cessation treatment development and refinement. Highlights: We examined anxiety sensitivity (AS) facets in relation to smoking measures. AS physical and cognitive concerns were related to tobacco dependence severity. AS social concerns were related to positive and negative reinforcement variables. All three AS facets were related to the greater abstinence-related problems. Additional treatment methods may benefit smokers high in AS social concerns.